Venom of several Indian green pit vipers: Comparison of biochemical activities and cross-reactivity with antivenoms. (30th April 2022) - Thakur, Susmita; Malhotra, Anita; Giri, Surajit; Lalremsanga, H.T.; Bharti, Omesh K.; Santra, Vishal; Martin, Gerard; Doley, Robin
Abstract: Green pit vipers, a name that can refer to several unrelated species, comprise a large group of venomous snakes found across the humid areas of tropical and sub-tropical Asia, and are responsible for most of the bite cases across this region. In India, green pit vipers belonging to several genera are prevalent in the northern and north-eastern hilly region, unrelated to species present in the peninsular region. In the present study, crude venom of representative species of green pit vipers present in the north and north-eastern hilly region of India ( Trimeresurus erythrurus, T. septentrionalis, Viridovipera medoensis, and Popiea popieorum ) were characterized to elucidate venom composition and venom variation. Profiling of crude venoms using SDS-PAGE and RP-HPLC methods revealed quantitative differences among the species. Further, in vitro biochemical assays reveal variable levels of phospholipase activity, coagulation activity, thrombin-like activity, fibrinogenolytic and haemolytic activity. This correlates with the pseudo-procoagulant effects on the haemostatic system of victims, which causes consumptive coagulopathy, frequently observed in patients bitten by green pit vipers. The immunoreactivity of Indian polyvalent antivenom and Thai green pit viper antivenom towards crude venoms were also evaluated by western blotting and inhibition of biochemical activities. The results exhibited poor efficacy of Indian polyvalent antivenom in neutralizing the venom toxins of crude venoms; however, Thai green pit viper antivenin (raised against the venom of Trimeresurus allbolabris, not present in India) showed higher immunoreactivity towards congeneric venoms tested. Analysis of green pit viper bite patients records from a community health centre in Assam, India, further revealed the inability of Indian polyvalent antivenom to reverse the extended coagulopathy featured. Graphical abstract: Image 1 Highlights: Green pit vipers from north-east and northern India showed considerable differences in venom profiles. Variation in biochemical activities causing pathophysiological effects were observed. Thai green pit viper monovalent antivenom showed better neutralization potency than Indian Polyvalent Antivenom.